PENGARUH EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP KADAR ENZIM ALT DAN AST MENCIT (Mus musculus) SETELAH PEMBERIAN KARBON TETRAKLORIDA - , PUTRA NUR HIDAYAT; , dr. Umi S. Intansari, M.Kes., Sp.PK (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Hepatoprotective properties of mangosteen pericarp (Garcinia mangostana L.) prevent free radicalinduced liver damage. Carbon tetrachloride (CCl4) form metabolite, lead to liver damage. Studies about hepatoprotective properties of mangosteen pericarp still continued. Objective: To know the effects of ethanol extract of mangosteen pericarp (EEMP) dose variation intake towards level of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) enzyme after CCl4 administration. Method: This study used quasi experimental with pretest-posttest control group design. Thirty male Mus musculus mice divided into six group randomly. K1 did not receive any treatment. K2, K3, K4, K5 and K6 were treated with CCl4, CCl4 and silymarin, CCl4 and 150mg/kgBW/day of EEMP, CCl4 and 300mg/kgBW/day of EEMP, CCl4 and 450mg/kgBW/day of EEMP, respectively for 6 weeks. ALT and AST measurement was used as liver damage indicator. Shapiro Wilk, ANOVA and paired t-test was used for statistical analysis. Result: ALT level average before treatment were 63,67Â±0,88U/L (K1)